2022
DOI: 10.1155/2022/8331688
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Efficacy of Electric Acupuncture in the Treatment of Premature Ejaculation Based on Testosterone Level

Abstract: Objective. To investigate the clinical efficacy and possible mechanism of electroacupuncture in the treatment of premature ejaculation. Methods. 50 cases of premature ejaculation patients who met the diagnostic criteria were randomly divided into 2 groups with 25 cases in each group. The observation group was treated with electroacupuncture, and the control group was treated with Longdan Xiegan decoction. The treatment period was 4 weeks. Ejaculation latency (IELT), sexual satisfaction score of patients, sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The data extracted from the included studies are summarized in Table 1 based on the type of intervention provided. Proportionately, 31.8% (n = 7) investigated different lifestyle, exercise and/or physical activities [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ]; 22.7% (n = 5) investigated herbal medicine supplements [ 65 , 66 , 67 , 68 , 69 ]; 18.2% (n = 4) investigated topical herbal applications [ 70 , 71 , 72 , 73 ]; 13.6% (n = 3) investigated acupuncture or electroacupuncture [ 74 , 75 , 76 ]; and 4.5% (n = 1) each investigated vitamin, mineral and/or nutraceutical supplements [ 77 ]; hyaluronic acid penile injection [ 78 ]; and music therapy [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The data extracted from the included studies are summarized in Table 1 based on the type of intervention provided. Proportionately, 31.8% (n = 7) investigated different lifestyle, exercise and/or physical activities [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ]; 22.7% (n = 5) investigated herbal medicine supplements [ 65 , 66 , 67 , 68 , 69 ]; 18.2% (n = 4) investigated topical herbal applications [ 70 , 71 , 72 , 73 ]; 13.6% (n = 3) investigated acupuncture or electroacupuncture [ 74 , 75 , 76 ]; and 4.5% (n = 1) each investigated vitamin, mineral and/or nutraceutical supplements [ 77 ]; hyaluronic acid penile injection [ 78 ]; and music therapy [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 22 studies included, 95.5% (n = 21) studies investigated the effect of TCAM treatments on patients with PE [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 78 , 79 ], with only 1 study investigating RE [ 77 ]. No studies were identified that investigated TCAM for treating DE, anejaculation or other EjDs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the acupuncture had a significant stronger ejaculation-delaying effect than sham acupuncture. Studies have shown that EA can improve the symptoms of premature ejaculation by regulating the level of serum testosterone ( 105 ). Although most studies on acupuncture in the treatment of sexual dysfunction have some methodological problems including small sample sizes and lack of blindness, almost all current studies can prove the efficacy of acupuncture in the treatment of sexual dysfunction, at least better than placebo.…”
Section: Clinical Effect and Mechanism Of Acupuncture On Male Inferti...mentioning
confidence: 99%